Agricultural technology adoption, productivity, and poverty reduction in Cameroon: A mediating analysis - Paul Akumbom; Mary Juliet Bime Egwu; Peter Ngek Shillie (Journal of Enterprise and Development (JED), 2023)
Purpose — Often people's hesitation to accept new technology stems from a misconception of what technology truly entails. Pictures of future robots and robotics typically spring to mind when people think of technology. Many poor nations rely heavily on agriculture for their survival. Most of the world's impoverished population works in agriculture and lives in rural regions. Indirectly and directly, it contributes to expanding industries and providing food for the world's population. This paper investigates the effects of agricultural technology adoption on poverty reduction.Method — The study adopted both the survey and causal research designs. The researcher employed purposive and snow ball sampling techniques. A total of 384 households were sampled for the study. Data for this study was gotten with the help of a structured questionnaire from household in Tubah Sub-Division of Cameroon and was analysed using inferential statistics.Result — This study revealed that consumable and durable inputs significantly positively affect agricultural productivity in the sub-division at 1% and 5% degree of significance respectively. The results further showed that agricultural productivity had a mediating positive effect on poverty reduction at 1% degree of significance.Contribution — Most studies on agricultural technology adoption in developing countries only focus on short-term impacts. In contrast, this study provides information on the long-term effects of technology adoption on farmers' livelihoods and the environment.